An effective combination of whole-exome sequencing and runs of homozygosity for the diagnosis of primary ciliary dyskinesia in consanguineous families - Ting Guo (Nature Portfolio, 2017)
Abstract Primary ciliary dyskinesia (PCD) is clinically characterized by neonatal respiratory distress, chronic sinusitis, bronchiectasis and infertility, and situs inversus in 50% of the patients. PCD is a result of mutations in genes encoding proteins involved in ciliary function, and is primarily inherited in an autosomal recessive fashion. Diagnosis of PCD is often a challenging task due to its high clinical and genetic heterogeneities. In the present study, we attempted to use whole-exome sequencing (WES) combined with runs of homozygosity (ROH) approaches to identify the genetic defects in four Chinese consanguineous families with clinical PCD. We successfully identified three recently acknowledged PCD genes: DYX1C1, CCNO and ARMC4, and one well-characterized PCD gene, DNAI1. Our study provides compelling evidence that WES in combination with ROH analysis is an efficient diagnostic tool for identifying genetic causes of PCD in consanguineous families. Furthermore, our work expands the genetic mutation spectrum in PCD, and provides the additional tools to better serve the counseling of the families with PCD.